PEMBERDAYAAN PEKERJA IMIGRAN INDONESIA DI SINGAPORE DALAM MEMBUAT HANTARAN PERNIKAHAN DARI SENI MELIPAT HANDUK - Prastiti Laras Nugraheni; Nurlaila Abdullah Mashabi; Elmanora; Dila Aprillia; Naura Dwinta Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract 70% of migrant workers in Singapore work in the informal sector as domestic helpers. However, there are still many Indonesian migrant workers who have problems due to low education and lack of competence. Therefore, it is necessary to improve the competence and knowledge of migrant workers to improve family welfare. One of the competencies that can be learned is the art of folding towels. The art of folding towels can not only help them organize their rooms where they work, but can also be a wedding gift business. This community service was carried out in August, and in collaboration with Elite Dreams Ins. PTE. LTD, Singapore and involved 16 migrant workers. This community service began with the preparation stage of making a towel art and towel creation guidebook as a training medium; the implementation stage was carried out with presentations, demonstrations, practices; and the evaluation stage. The evaluation results showed an increase in participants' knowledge and skills in making gifts from the art of folding towels shown by all participants, there was an increase in pre-test and post-test scores of 100%, and participant satisfaction with the resource person was 81.3%, training materials 93.8%, methods 87.5%, facilities 100%, and usefulness 100%. It is hoped that this community service will not only make migrant workers more capable in their jobs but also improve family welfare through wedding gift businesses. Keywords: the art of folding towels ; migrant workers; wedding gift Pekerja migran di Singapura 70% bekerja di sektor informal sebagai asisten rumah tangga. Namun masih banyak pekerja migran Indonesia yang bermasalah akibat pendidikan yang rendah dan kurangnya kompetensi yang dimiliki. Oleh karena itu diperlukan peningkatan kompetensi dan pengetahuan para pekerja migran untuk meningkatkan kesejahteraan keluarga. Salah satu kompetensi yang bisa dipelajari adalah seni melipat handuk. Seni melipat handuk bukan hanya dapat membantu mereka dalam menata kamar di tempat mereka bekerja, namun dapat menjadi usaha hantaran pernikahan. Pengabdian kepada masyarakat ini dilaksanakan pada bulan agustus, dan bekerjasama dengan Elite Dreams Ins. PTE. LTD, Singapore serta melibatkan 16 orang pekerja migran. Pengabdian kepada masyarakat ini dimulai dengan tahapan persiapan membuat buku panduan towel art dan towel creation sebagai media pelatihan ; tahap pelaksanaan dilakukan presentasi, demonstrasi, praktik ; dan tahap evaluasi. Hasil evaluasi menunjukkan peningkatan pengetahuan dan keterampilan peserta dalam membuat hantaran dari seni melipat handuk yang ditunjukkan seluruh peserta terjadi peningkatan nilai pre-test dan post-test sebesar 100% , dan kepuasan peserta terhadap narasumber sebesar 81,3%, bahan pelatihan 93,8%, metode 87,5%, fasilitas 100%, dan kebermanfaatan sebesar 100%. Diharapkan pengabdian masyarakat ini tidak hanya membuat pekerja migran semakin cakap dalam pekerjaannya namun juga meningkatkan kesejahteraan keluarga melalui usaha hantaran pernikahan. Kata Kunci: hantaran pernikahan; pekerja migran; seni melipat handuk